Prevalence of brucellosis and associated risk factors in dairy cattle in Maekel and Debub regions, Eritrea - Efrem, G.H.; Mihreteab, B.; Ghebremariam, M.K.; Okbamichael, T.; Ghebresilasie, Y.; Mor, Siobhan M.; Mamo, G. (Frontiers Media, 2023)
Introduction: Brucellosis is a zoonotic disease with worldwide distribution. It is considered endemic in Eritrea, however, the current prevalence status and related risk factors in animals are unknown. The objective of this study was to determine the prevalence of and risk factors for brucellosis in dairy cattle in Maekel and Debub regions, Eritrea.